The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings FUZZING 2022 - 1st International Fuzzing Workshop 2022
DOI: 10.14722/fuzzing.2022.23006
|View full text |Cite
|
Sign up to set email alerts
|

NSFuzz: Towards Efficient and State-Aware Network Service Fuzzing

Abstract: As the essential component responsible for communication, network services are security-critical, and it is vital to find v u lnerabilities i n t h em. F u zzing i s c u rrently o n e o f the most popular software vulnerability discovery techniques, widely adopted due to its high efficiency and low false positives. However, existing coverage-guided fuzzers mainly aim at stateless local applications, leaving stateful network services underexplored. Recently, some fuzzers targeting network services have been pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Our results for all text-based protocols in the PRO-FUZZBENCH protocol fuzzer benchmark [33] demonstrate the effectiveness of the LLM-guided approach: Compared to the baseline (AFLNET [36]) into which our approach was implemented, our tool CHATAFL covers almost 50% more state transitions, 30% more states, and 6% more code. CHATAFL shows similar improvements over the state-of-the-art (NSFUZZ [38]). In our ablation study, starting from the baseline we found that enabling (i) the grammar extraction, (ii) the seed enrichment, and (iii) the saturation handler one by one allows CHATAFL to achieve the same code coverage 2.0, 4.6, and 6.1 times faster, respectively, as the baseline achieves in 24 hours.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…Our results for all text-based protocols in the PRO-FUZZBENCH protocol fuzzer benchmark [33] demonstrate the effectiveness of the LLM-guided approach: Compared to the baseline (AFLNET [36]) into which our approach was implemented, our tool CHATAFL covers almost 50% more state transitions, 30% more states, and 6% more code. CHATAFL shows similar improvements over the state-of-the-art (NSFUZZ [38]). In our ablation study, starting from the baseline we found that enabling (i) the grammar extraction, (ii) the seed enrichment, and (iii) the saturation handler one by one allows CHATAFL to achieve the same code coverage 2.0, 4.6, and 6.1 times faster, respectively, as the baseline achieves in 24 hours.…”
Section: Introductionmentioning
confidence: 68%
“…A mutation-based protocol fuzzer [36], [38] uses a set of pre-recorded message sequences as seed inputs for mutation. The recording ensures that the message structure and order are valid while mutational fuzzing will slightly corrupt both [36].…”
Section: A Protocol Fuzzingmentioning
confidence: 99%
See 3 more Smart Citations